2008
DOI: 10.1007/s00784-008-0230-8
|View full text |Cite
|
Sign up to set email alerts
|

Tooth brushing habits in uninstructed adults—frequency, technique, duration and force

Abstract: Professional recommendations for individual oral hygiene mostly include tooth brushing at least twice daily for 2-3 min with gentle force using the Bass technique or modifications of it. This study evaluated whether habitual tooth brushing actually meets these standards. Uninstructed adults (n = 103; mean age 31 +/- 6 years; 61 female, 42 male) with habitual manual tooth brushing were given a self-administered questionnaire about the frequency of brushing and a computer system recorded their brushing technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
4
16

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 17 publications
6
139
4
16
Order By: Relevance
“…Annette, et al [27] reported gender differences of brushing force was not statistically recognized. By contrast, Ganns, et al [20] reported the only significant gender difference was in brushing force, which was slightly higher in males. In this study, the mean brushing force of self-brushing was 1.85N in males and 1.32N in females.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Annette, et al [27] reported gender differences of brushing force was not statistically recognized. By contrast, Ganns, et al [20] reported the only significant gender difference was in brushing force, which was slightly higher in males. In this study, the mean brushing force of self-brushing was 1.85N in males and 1.32N in females.…”
Section: Discussionmentioning
confidence: 84%
“…Burgett, et al [29] described that subjects with wedge-shaped lesions had significantly higher mean brushing force than subjects without cervical wear (2.9 versus 2.1N). From these studies it has been recommended that tooth brushing force should not exceed 3N [20]. Akgul, et al [30] stated the prevalence of tooth brushing abrasions was seen more frequently in males than in females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various surgical and non surgical options are available for the same. The dentists should also discuss and explain to the patients about the proper brushing techniques, as this will go a long way in preventing recession [8].…”
Section: Resultsmentioning
confidence: 99%